STUDY THE EFFECT OF (Ti) ADDITION ON THE MICROSTRUCTURE OF EUTECTIC Al-12%Si ALLOY - Mustafa Ahmed Rijab (Diyala Journal of Engineering Sciences, 2009)
The aim of this research is to investigate the effect of addition of titanium (0.05 and 0.1) % on the microstructure of AL – 12% Si alloy, as well as the effect of long term homogenization (525 oC) on the developed microstructures. The microstructure results showed that the addition of 0.05% Ti exhibited a partial modification of the microstructure, while the addition of 0.1% Ti to the alloy showed a marked effect on the modification. Also the results showed that the transformation of silicon (Si) from needle or fibrous shape to spheriodal shape was observed during homogenization of the alloys. The spheroid shape of silicon (Si) particles was obtained via five different stages, namely; growth, fragmentation, spherodization, growth and stabilization of the spherodized silicon.